The Research on Utilization and Interoperability of XBRL Taxonomy Elements of Listed Companies Financial Report (Global Journal of Human-Social Science, 2014)
This article is based on the research on utilization and interoperability of Chinese XBRL taxonomy elements, focusing on the improvement of the insufficient XBRL taxonomy elements. The authors believe that increase the number of XBRL taxonomy elements can enhance the interoperability of financial reports and accuracy of compiling XBRL software elements.
Keywords: XBRL taxonomy; elements utilization; elements interoperability